Analisis Pengaruh Fluktuasi Kurs Valuta Asing dan Kebijakan Harga Bahan Bakar Minyak dalam Periode 2000-2008 terhadap Kinerja PT Astra Internasional di Indonesia - Mohamad Heykal; Theresa Febrona; Hidayatullah Hidayatullah (Bina Nusantara University, 2011)
The fourth quarter in 2008 is the peak of Global Monetary Crisis, which is the decreasing of liquidity in companies around the world. The crisis also affected towards fluctuation of world petroleum price. Automotive industry in Indonesia was also affected towards cost of foreign exchange fluctuation and petroleum price due to the crisis. PT Astra International, Tbk. is assumed to represent automotive industry in Indonesia. The research is done through literature research and financial and sales report analysis in 2000-2008. The performance reduction is directly connected by the decreasing of earnings, especially in motor vehicle and parts sale in those years and also the increasing of cost of production, due to the increasing of import fee and transportation cost. Foreign exchange fluctuation and petroleum price directly affects the work performance of PT Astra Internasional.